Explaining Recruitment Stochasticity at a Species’ Range Margin - Westerbom, Mats; Kraufvelin, Patrik; Mustonen, Olli; Díaz, Eliecer (Frontiers in Marine Science, 2021)
Advancing our understanding of how environmental variability affects the distribution of organisms is crucial for ecology and conservation. The exploration of changes in demographic patterns close to species distribution margins is important as populations here may provide a window into future population changes also elsewhere. However, the knowledge of factors causing recruitment variation is still inadequate in many systems and this deficiency is particularly evident close to species’ distribution borders. We studied the spatiotemporal variability in recruit-adult dynamics in a blue mussel, Mytilus trossulus, population to get insights into how environmental variables drive variation in recruitment and how this variability affects adult population growth. Thirty sites along a wave exposure gradient were monitored during four consecutive years. From each site, mussels were collected both from artificial recruitment units and from natural mussel beds. Our results showed high year-to-year variation in recruitment strength with high spatial variation. Mussel recruitment to artificial units and later recruitment to the benthos correlated highly. Juvenile abundances one year later paralleled prior recruitment strengths and caused synchronous but time-lagged changes in adult cohorts. Seawater salinity was the strongest predictor for recruitment variation, whereas sea temperature and wave exposure had low predictive power for this early life stage. For juveniles and for adults in the benthos, wave exposure explained the variation best, whereas temperature and especially salinity explained less. The results indicate that (a) the studied blue mussel population is strongly driven by variation in recruitment strength that (b) drives the size of the later cohorts, and the population is possibly even (c) recruitment limited in some years. Our study predicts a challenging future for this range population, resulting from a higher frequency of recruitment failure caused by a deteriorating sea climate. Knowledge about factors underlying variation in recruitment is thus essential for forecasting the future of this range population and for conserving its future state.